A Knowledge Mobilization Initiative Pilot in the Library - Alison J. Moore; Lupin Battersby; Valorie Crooks (Partnership: The Canadian Journal of Library and Information Practice and Research)
Over the last twenty years knowledge mobilization (KM) is increasingly a priority for researchers, funders, and universities. As KM emphasizes non-traditional forms of mobilization and encourages approaching research differently (e.g. co-production) there is a natural fit with advancements in academic librarianship such as digital scholarship. The goal of KM is to increase the use and positive impact of research beyond academia. Many researchers, required to plan and do KM as part of the funding requirements, need additional supports to learn about and mobilize their research beyond traditional approaches; academic institutions are responding with developing support services or roles in the institution. Approaches to these services are diverse, some centralized, some faculty or department specific, some dedicated roles, others added on to existing roles. In this paper we describe a pilot project to support KM at one Canadian university. Specifically, we share the development, initiation, and program model of a KM support unit within an academic library. We make the case for the importance of physical location of this type of service, the value the library adds to this service, and other lessons learned through this pilot project.